Women in Iraq between requirements, challenges and empowerment programs - Mastour, Sohaila; Khalaf, Sadiq (The Gulf Economist, 2024)
Empowering women in Iraq and their participation in the public life of the Iraqi society, as they represent 50% of the population of this society. Therefore, researching this topic could be considered a very fruitful process, as women have an active contribution to the sustainable development process, provided that the requirements are met and the challenges that stand in the way of taking their natural role, opportunity and right in society, especially In light of the recent changes that have occurred in the Iraqi society after 2003, and it has real programs to empower them as a basic human right, as the issue of empowering women in Iraqi society and how and the programs through which empowerment is carried out with the means to achieve this is one of the vocabulary of integrated development in society. The research addressed the problem of women’s participation in all economic, social and political fields, which is still weak even though they have proven their efficiency when they are in a position of responsibility. Therefore, there is an urgent need to be a real partner in the progress and building of society under the premise that all attempts are still poor and do not rise to the status Women, their role and status in society, noting that Iraqi women can contribute to achieving sustainable development at all levels, if they are provided with the vocabulary of empowerment in a real and realistic way. Therefore, the research aims to give solutions to advance the situation of women in Iraq so that they can take their natural position and participate economically, socially and culturally in Society, to reduce the difficulties that stand in the way of this true role of Iraqi women, especially since women represent 58.2% of the total economically active population.